A simplified combination antiretroviral therapy regimen enhances adherence, treatment satisfaction and quality of life: results of a randomized clinical trial. Issue 5 (11th November 2013) - Langebeek, N; Sprenger, HG; Gisolf, EH; Reiss, P; Sprangers, MAG; Legrand, JC; Richter, C; Nieuwkerk, PT
<x xml:space="preserve">Abstract</x> Objectives The aim of the study was to investigate the effect of a simplified regimen, in terms of reducing pill burden, dietary requirements and possible adverse effects, on patients' adherence, treatment satisfaction and quality of life (QoL). Methods Antiretroviral‐naïve patients who achieved a viral load < 50 HIV‐1 RNA copies/ml after induction therapy with twice‐daily (bid) lopinavir/ritonavir (LPV/r) and fixed‐dose zidovudine (ZDV)/lamivudine (3TC) (CBV) were randomly assigned to continue CBV/LPV/r or switch to fixed‐dose ZDV/3TC/abacavir (TZV). Patients completed standardized questionnaires on adherence, treatment satisfaction and QoL at randomization (between weeks 12 and 24) and at weeks 48, 72 and 96. Results Patients on CBV/LPV/r were more likely to have skipped medicines in the last week (P = 0.035) and during the preceding weekend (P = 0.027) than patients on TZV. Patients on CBV/LPV/r were significantly less satisfied with the convenience of their treatment (P = 0.004) and tended to be less satisfied with the side effects of their treatment (P = 0.091) and continuation of their present treatment (P = 0.056) than patients on TZV. Patients on CBV/LPV/r reported significantly lower levels of role functioning (P = 0.013) than patients on TZV. Conclusions In this randomized controlled trial, simplification of therapy to fixed‐dose TZV among patients with suppressed HIV RNA was perceived to be more convenient, and resulted in improved adherence and better role functioning, than continuing treatment with CBV/LPV/r.